Value of pre-existent bacterial colonization in patients with advanced/relapsed ovarian neoplasms undergoing cytoreductive surgery: a multicenter observational study (BONSAI). Issue 10 (18th October 2020) - Fotopoulou, Christina; Rinne, Natasha; Ghirardi, Valentina; Cunnea, Paulea; Drosou, Anastasis; Tzovaras, Dimitrios; Giudice, Maria Teresa; Scambia, Giovanni; Fagotti, Anna
Abstract : Objective: As an increasing number of patients with advanced/relapsed ovarian cancer need extensive cytoreductive procedures, there is an increasing number of complex cases collected in accredited tertiary cancer centers. With nosocomial infections and bacterial colonizations being a significant challenge in these patient cohorts, we aimed to evaluate the risk such infections pose to surgical outcome. Methods: Prospective assessment of pathological bacterial colonization (vaginal, umbilical/groin, intraperitoneal, urine, oral/nose cavity) in patients who underwent open cytoreductive surgery for advanced/relapsed ovarian cancer in two large European tertiary referral centers for gynecologic malignancies. We recruited patients at initial diagnosis with International Federation of Gynecology and Obstetrics (FIGO) stage III and IV ovarian cancer and patients undergoing surgery for relapse. Swabs or cultures were taken from the following sites: vagina, groin and/or umbilicus, urine, intraperitoneal, mouth and/or nose. Only evidence of pathogenic bacteria was considered positive for bacterial colonization. Results: A total of 172 primary advanced (70.9%) or relapsed (29.1%) ovarian cancer patients were included; 63.4% of them had received chemotherapy±additional targeted agents (16.3%) by the time of cytoreduction. 39.5% of the patients had a long-term vascular access line in situ. A bowel resection was performed in 44.8% and a splenectomy in 16.3% of the patients. Predefined surgical morbidity and mortality were 22.3% and 0%, respectively. Forty-one patients (23.8%) screened positive for pathogenic bacterial colonization with the presence of long-term intravenous access as the only independent risk factor identified (OR 2.34; 95% CI 1.05 to 5.34; p=0.04). Type of systemic treatments, previous bowel resections, previous hospitalizations, and patient demographics did not appear to significantly impact the risk of bacterial colonization. Furthermore, pathogenic bacterial colonization was shown to have no significant effect on peri-operative infection-related complications such as abscesses, wound infection, pneumonia, relaparotomy, or anastomotic leak. Conclusions: A total of 24% of patients undergoing cytoreductive surgery for ovarian cancer were confirmed positive for pathogenic bacterial colonization. The presence of long-term intravenous access was identified as the only significant risk factor for that, however the presence of pathogenic bacterial colonization per se did not seem to adversely affect outcome of cytoreductive effort or increase perioperative infection related complications.